Computer simulations of statistical models and dynamic complex systems - J.S. Sá Martins (Brazilian Journal of Physics, 2004)
These notes concern the material covered by the authors during 4 classes on the Escola Brasileira de MecânicaEstatística, University of São Paulo at São Carlos, February 2004. They are divided in almost independentsections, each one with a small introduction to the subject and emphasis on the computational strategy adopted.